Labor Tax Avoidance and Its Determinants: The Case of Mafia Firms in Italy - Ravenda, Diego (Journal of business ethics, 2015)
This paper develops two new measures of labor tax avoidance (LTAV) based on social contribution expenses reported in financial statements and tests them and their determinants within a sample of 224 Italian firms defined as legally registered Mafia firms (LMFs) due to having been confiscated at some point by judicial authorities, in relation to alleged connections with Italian organized crime. Overall, our results reveal that before confiscation LMFs engage more in LTAV than lawful firms do, whereas after confiscation there is no significant difference between both types of firm. Furthermore, we find that several factors have a significant influence on the probability of engaging in such a practice. This study can enhance further research on the effectiveness of our measures and on the determinants of LTAV in other contexts and for other types of firms. Moreover, these measures can be added to the other direct and indirect methods commonly employed to measure and detect undeclared work representing a primary means of LTAV. Finally, our study allows inferring conclusions on the relation between corporate social responsibility and tax avoidance, suggesting that socially irresponsible firms, such as LMFs, are more likely to adopt this practice.